Correction: Selective light driven reduction of CO2 to HCOOH in water using a MoV9n (n = 1332–3600) based soft-oxometalate (SOM). Issue 9 (17th January 2022) - Barman, Soumitra; Das, Santu; S. S., Sreejith; Garai, Somnath; Pochamoni, Ramudu; Roy, Soumyajit
Abstract : Correction for 'Selective light driven reduction of CO2 to HCOOH in water using a MoV9 n ( n = 1332–3600) based soft-oxometalate (SOM)' by Soumitra Barman et al., Chem. Commun., 2018, 54, 2369–2372, DOI: ; 10.1039/C7CC09520A .